Synthesis and Characterization of Graphene Oxide Nanosheets by Electrochemical Exfoliation Method and its Antibiofilm Activity against Pseudomonas aeruginosa - Husam N. Abbas (Journal of Global Pharma Technology, 2020)
In this work, the Graphene oxide (GO) nanosheets were synthesized by a electrochemical exfoliation method. The morphological, structure and optical properties were investigated by using Field emission scanning electron microscope (FE-SEM), X-ray diffraction (XRD), Raman spectroscopy, FTIR and UV-VIS spectroscopy. FE-SEM images of GO nanosheets confirmed the presence of layered structure. The crystalline size and number of layers of GO nanosheets were estimated by XRD analysis. The UV-VIS spectrum of GO nanosheets shows maximum and shoulder absorption peaks. The oxidation of graphene was confirmed via FTIR analysis by the appearance of functional groups of oxygen. Raman analysis showed the formation of peaks D, G and 2D. The antibiofilm activity of different concentrations of GO nansheets against Pseudomonas aeruginosa (P. aeruginosa) as a model of more antibiotics resistant Gram-negative bacteria was investigated. These results confirm that the GO nanosheets material damages the biofilm of P. aeruginosa. Therefore, It can be considered as an anti-bacterial material.Keywords: Graphene Oxide, Nanosheet, Electrochemical Exfoliation, Antibiofilm, Pseudomonas aeruginosa.